The Correlation Between Students‟ Linguistic Intelligence and Their English Speaking Skill Achievement - Amin Mubarok (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to identify whether there is a significant correlation between students’ linguistic intelligence and their English speaking skill achievement among fourth semester students of the English Education Department, Faculty of Tarbiyah and Teachers Training, State Islamic University of Syarif Hidayatullah Jakarta. Methodology: This study used correlational research with library research and field research methods. The population consisted of fourth semester students of the English Education Department academic year 2009. Data were collected through linguistic intelligence tests and English speaking achievement scores. Data analysis used Product Moment Correlation formula to determine the relationship between variables. Main Findings: The result showed that the correlation coefficient between students’ linguistic intelligence and their English speaking skill achievement was 0.042, which belongs to a very low correlation level. It indicates that there was no significant correlation between students’ linguistic intelligence and their English speaking skill achievement in this study. Novelty/Originality of this study: This study provides a specific analysis of the relationship between linguistic intelligence based on Howard Gardner’s multiple intelligences theory and English speaking achievement in higher education students. It contributes new insight that linguistic intelligence cannot be simply measured through academic potential tests and may not directly determine speaking performance